2021
DOI: 10.5755/j01.sace.29.2.28576
|View full text |Cite
|
Sign up to set email alerts
|

Past and Future Trends on the Effects of Occupant Behaviour on Building Energy Consumption

Abstract: In recent decades, the need for an accurate evaluation of energy use in buildings has become increasingly growing due to the rise in environmental awareness and political pressure around the world. The estimation of energy consumption is, therefore, a crucial criterion during building early-stage design. This paper investigates the recent trends and achievements in modelling occupant behaviour in energy simulation studies and aims to highlight achievements and research gaps in the domain. This study presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…20 However, there is a need for more nuanced research into occupant behaviour, particularly in the context of energy consumption, to inform COVID-19 strategies. 21 Regarding the HVAC system, numerous studies examining the impact of HVAC system operation on COVID-19 transmission and indoor air quality has drawn the attention of several researchers. Allen and Ibrahim 22 emphasized the importance of increasing outdoor air ventilation and enhancing filtration to limit airborne transmission of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, there is a need for more nuanced research into occupant behaviour, particularly in the context of energy consumption, to inform COVID-19 strategies. 21 Regarding the HVAC system, numerous studies examining the impact of HVAC system operation on COVID-19 transmission and indoor air quality has drawn the attention of several researchers. Allen and Ibrahim 22 emphasized the importance of increasing outdoor air ventilation and enhancing filtration to limit airborne transmission of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, there is a need for more nuanced research into occupant behaviour, particularly in the context of energy consumption, to inform COVID-19 strategies. 21…”
Section: Introductionmentioning
confidence: 99%
“…This condition serves no beneficial purpose and contributes to the wastage of electricity due to human negligence. Previous studies have shown that occupant presence and behavior in buildings have a major impact on energy consumption for lighting [ 5 ]. Thus, careless user behavior can influence the energy efficiency of a building by one-third, which is a significant contributing factor [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buildings are one of the main contributors to excessive energy consumption and carbon emission [13]. This sector plays a critical role in the energy context and contributes significantly to both overall greenhouse gas emissions and global energy consumption, according to the EIA [14].…”
Section: Introductionmentioning
confidence: 99%